Improving Student’s Vocabulary Through Song and Movement - Fatih Al Fauzi; Isna Sholihatul Hamidah (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2025)
This research is based on the phenomenon of students' lack of vocabulary in the language learning process. Therefore, the author examined the process of vocabulary acquisition using songs and movements to provide new insights into learning vocabulary. The purpose of this study is to determine whether songs and movements are effective in developing students' vocabulary and to understand students' perceptions of vocabulary learning using these methods. In collecting data, the author employed classroom action research (CAR), administered pre-tests and post-tests, and conducted interviews. The participants consisted of 24 seventh-grade students at SMP Al Hikmah Jember. The results of the study showed progress in vocabulary learning through songs and movements, evidenced by the average pre-test score (62.03) and post-test score (75.39). The majority of students responded positively to vocabulary learning through songs and movements. This method helps students easily memorize words and creates a comfortable learning environment. However, some students prefer learning by writing down and memorizing words.